A new species of the genus Trichoformosomyia Townsend from Malaysia (Diptera: Tachinidae) - Tachi, Takuji (Zootaxa, 2013)
A new species of Trichoformosomyia, T. abbreviata sp. nov., is described from Sabah, Malaysia. Trichoformosomyia sauteri Baranov is redescribed and it is newly recorded from China, Vietnam and Japan. A key to the three known species of Trichoformosomyia is given and monophyly of the genus is briefly discussed based on adult morphology.